SUBDWARFS: ABUNDANCE OF LIGHT ELEMENTS - Mishenina, T. V.; Klochkova, V. G.; Panchuk, V. E. (Одеські астрономічні публікації, 2017)
CNO abundances in the atmospheres of seven metal-deficient stars were derived by model atmosphere method on the basis of high dispersion Echelle spectra obtained using the 6-m telescope of the Special Observatory of the Russian Academy of Sciences. The O abundances are derived from lines of lR-triplet Ol 7773 Å. The C2(0,1) bandhead of the Svaan A3IIg – X3llg system, at 5635.5 Å is used to derive the C abundances. To derive the nitrogen abundances, the CN red system A2ll-X2Σ was used. the CN(5,1) 6332.18 Å and 6478.48 Å were considered. The obtained [O/Fe] values confirm the trend of [O/Fe] vs [Fe/H]. For stars of our sample with [Fe/H] > -1.00 we found that nitrogen is overabundant relative to iron; carbon - underabundant.